Transposon Mutagenesis of the Obligate Intracellular Pathogen Rickettsia prowazekii - Qin, Aiping (American Society for Microbiology, 2004)
Genetic analysis of Rickettsia prowazekii has been hindered by the lack of selectable markers and efficient mechanisms for generating rickettsial gene knockouts. We have addressed these problems by adapting a gene that codes for rifampin resistance for expression in R. prowazekii and by incorporating this selection into a transposon mutagenesis system suitable for generating rickettsial gene knockouts. The arr-2 gene codes for an enzyme that ADP-ribosylates rifampin, thereby destroying its antibacterial activity. Based on the published sequence, this gene was synthesized by PCR with overlapping primers that contained rickettsial codon usage base changes. This R. prowazekii-adapted arr-2 gene (Rparr-2) was placed downstream of the strong rickettsial rpsL promoter (rpsL(P)), and the entire construct was inserted into the Epicentre EZ::TN transposome system. A purified transposon containing rpsL(P)-Rparr-2 was combined with transposase, and the resulting DNA-protein complex (transposome) was electroporated into competent rickettsiae. Following selection with rifampin, rickettsiae with transposon insertions in the genome were identified by PCR and Southern blotting and the insertion sites were determined by rescue cloning and inverse PCR. Multiple insertions into widely spaced areas of the R. prowazekii genome were identified. Three insertions were identified within gene coding sequences. Transposomes provide a mechanism for generating random insertional mutations in R. prowazekii, thereby identifying nonessential rickettsial genes.